Is Acupressure Effective To Treat Pruritus In Hemodialysis Patients? A Literatur Review - Yuanita Panma; Hertuida Clara; Siti Nurhayati (STIKep PPNI Jawa Barat, 2022)
Aims: Chronic kidney diseases effects make the pruritus prevalence in hemodialysis patients relatively high. Several studies have been conducted to determine the effect of acupressure on complaints of uremic pruritus. However, it is still debatable how acupressure relief pruritus complains regarding the duration of acupressure. This study aims to identify the effectiveness of acupressure against pruritus based on previous studies. Materials and Methods: An electronic literature search was conducted to identify studies that matched the inclusion criteria. The electronic databases used in this research are Wiley online library, Clinical key, ProQuest, EBSCO, and Google Scholar. The keyword used was “acupressure”, “pruritus”, “itch”, and “hemodialysis”. Results: We found 1,983 articles based on keywords, and five articles met the inclusion criteria after conducting the article selection process. Three of the four experimental studies measured pruritus using a visual analog scale, and one used a numerical scale. One study applied auricular acupressure, and four studies used acupressure. Four studies have shown that acupressure effectively reduces the scale of pruritus. One study showed no significant difference between acupressure, sham control, and negative control groups in two weeks of intervention in the severity of pruritus (p=0.66). Conclusion: Acupressure is effective in treating uremic pruritus and nurse can applied acupressure as a non-pharmacological intervention for pruritus in hemodialysis patients.